THE COMMENTING ON THE “NASAYIM UL MUKHABBAT” - Khayrullayevna, Istamova Gavhar (The journal of contemporary issues in business and government, 2021)
In the following article the etiquette of tariqat as it appears in the antology of “Nasayim ul mukhabbat” of Navai, the ways of perfection of soul and the pillars of mujahada is analysed. One of the requirrements of Islam fasting - is advantages of hungriness, insomnia, awareness, its status in the spiritual life is substantiated based on the treatises of the Navai.